Artificial Intelligence and data analytics in impact investing: Emerging opportunities for social enterprises (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The rapid advancement of Artificial Intelligence (AI) and Data Analytics has transformed the global financial ecosystem, particularly in the field of impact investing and social entrepreneurship. Impact investing refers to investments made with the intention of generating measurable social and environmental benefits alongside financial returns. Social enterprises, which aim to solve societal challenges through innovative business models, increasingly rely upon technology-driven financial systems to expand their operations and improve impact measurement. Artificial Intelligence and data-driven analytics provide sophisticated tools for assessing investment risks, predicting social outcomes, identifying underserved markets, and optimizing sustainable financial decision-making.This study critically examines the emerging role of AI and data analytics in impact investing and explores how these technologies create new opportunities for social enterprises. The article evaluates the integration of machine learning, predictive analytics, big data, blockchain-based transparency systems, and automated impact assessment models within the impact investment ecosystem. It further analyses legal, ethical, and governance challenges associated with algorithmic bias, data privacy, transparency, accountability, and digital inequality.The study adopts a doctrinal and analytical methodology based on secondary sources including academic literature, international reports, policy documents, and financial technology studies. It concludes that AI and data analytics have the potential to significantly enhance transparency, scalability, and effectiveness in impact investing. However, ethical regulation, responsible AI governance, and inclusive digital infrastructure are necessary to ensure sustainable and equitable growth of social enterprises globally.